Interaction between C60 and gases under pressure - Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
A brief review is given of the interaction between fullerite C60 and various gases under elevated pressure. Subjects discussed include the formation of ordered interstitial gas-fullerene compounds, reactions between intercalated gases and fullerene molecules to form new endohedral andexohedral compounds, and changes in the structure and properties of C60 because of intercalatedgas atoms or molecules.